Investing Neonatal Septic Arthritis: A Systematic Review - Neelam Harsha; Rakesh Kotha; Alimelu Madireddy (Mazandaran University of Medical Sciences, 2024)
Background and Objectives: Septic arthritis is an uncommon condition in neonates. It is a serious disorder, especially because of the possibility of sequelae, if not identified and treated early. In addition, due to the rarity of this condition in neonates and the paucity of signs and symptoms, the diagnosis of septic arthritis is more difficult in older children. The published literature is limited to case series, which is why the purpose of this systematic review is to provide a comprehensive summary of neonatal septic arthritis based on the existing literature. This study identifies the changing trends over time, specifically focusing on intravenous cannulation as a major risk factor that led to the undertaking of the study. Methods: The preferred reporting items for systematic reviews and meta-analyses protocol guidelines were used in this study. Three search engines were used for 239 articles. A total of 26 studies were screened in full text, of which 16 articles underwent quantitative analysis. Due to limited data and heterogeneous reporting, the data were summarized descriptively. Results: The total number of babies and joints studied was 307 and 313, respectively, of which the proportion of male babies was mentioned in 12 case series, accounting for 136(228) (60% [42%-71%]) subjects. The most common presenting symptoms were swelling at the involved joint, erythema, and decreased range of motion in variable order. The most common site of involvement was the hip joint (42%), followed by the knee joint (27%). Staphylococcus aureus (40%) was the most commonly cultured pathogen, followed by Klebsiella (18%). Antibiotics were reported in only 12% (38 babies) of the cases. Open surgery was performed on 16% of the 49 babies. The rest of the babies responded to joint aspiration and irrigation, with or without immobilization. Prompt laboratory and radiographic evaluations could help reduce delays in diagnosis and improve outcomes. Blood and tissue cultures were positive in most of the cases. Previous culture reports for the same unit guide the addition of empirical antibiotics. Conclusions: In our case series, the majority of the babies were premature. The most common joint involved is the hip joint. The most common underlying cause is sepsis and catheterization. Intravenous canulation is also a major risk factor because of the continuity of metaphysis and epiphysial vessels. The most common presenting symptom is local signs. Unexplained fever and irritability make it better to look for a local examination of joints. Follow-up is mandatory as a long-term sequel is more.